Analisis Sistemik Kebangkrutan Dapur Mami Medan dan Perumusan Kerangka Resiliensi Digital : Penelitian - Yoga Fitriana; Muhammad Irfan Sarif; Yohannes France Limbong; Lamsihar Banjarnahor (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study uses a qualitative approach to in-depth examine the failure of the culinary MSME "Dapur Mami" in Medan City, which in 2021 demonstrated superior performance through product exports to international markets. The study aims to identify the main factors causing the bankruptcy and formulate an information systems (IS)-based resilience framework for risk mitigation. Data were collected through in-depth interviews and digital artifact review, then analyzed using thematic analysis. The results identified four main causes of failure: unstable export market dominance, weak production and supply chain management, suboptimal digital marketing and customer relationship management (CRM), and the absence of an information system supporting financial analysis and decision-making. This bankruptcy reflects a systemic failure resulting from premature expansion without operational readiness and digital infrastructure. As a contribution, this study develops a Digital Resilience Framework for Culinary MSMEs (KRD-UK) based on digital transformation and risk management, which encompasses strengthening the domestic market, automation-based market diversification, and data-driven business performance optimization, to increase the resilience of culinary MSMEs in facing global market dynamics.